2021
DOI: 10.1007/s10433-021-00669-9
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of home care utilization among the Swedish old: nationwide register-based study

Abstract: Since the 1990s, Sweden has implemented aging-in-place policies increasing the share of older adults dependent on home care instead of residing in care homes. At the same time previous research has highlighted that individuals receive home care at a higher age than before. Consequently, services are provided for a shorter time before death, increasing reliance on family and kin as caregivers. Previous studies addressing how homecare is distributed rely primarily on small surveys and are often limited to specif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 37 publications
(45 reference statements)
1
13
0
Order By: Relevance
“…Such residential arrangements are likely to be associated with differences in physical and social activity that may be consequential for health and cognition. [ 15 , 26 ] For example, the reported incidence of falls per person-year (a key indicator of frailty) is nearly twice as high in Sweden compared to Spain. The proportion of older adults receiving longer-term care at home differs substantially across countries, ranging from 8% in the USA to 12% in Sweden and the UK.…”
Section: Demographic Characteristics Of Ltcf Residentsmentioning
confidence: 99%
See 3 more Smart Citations
“…Such residential arrangements are likely to be associated with differences in physical and social activity that may be consequential for health and cognition. [ 15 , 26 ] For example, the reported incidence of falls per person-year (a key indicator of frailty) is nearly twice as high in Sweden compared to Spain. The proportion of older adults receiving longer-term care at home differs substantially across countries, ranging from 8% in the USA to 12% in Sweden and the UK.…”
Section: Demographic Characteristics Of Ltcf Residentsmentioning
confidence: 99%
“…These outcomes reflect individual preferences as well as public policies aimed at encouraging residence at home rather than in LTCFs whenever possible. [ 26 , 27 ]. Older adults face an array of residential options depending on income and health status, including retirement communities and group homes for those who can live independently, assisted living for those with specific needs or disabilities, care homes for the frail and cognitively impaired, skilled nursing facilities for those with severe illness, and hospices to provide end-of-life care.…”
Section: Demographic Characteristics Of Ltcf Residentsmentioning
confidence: 99%
See 2 more Smart Citations
“…We selected four factors to assess potential sociodemographic impacts on use of social services. Sex and living alone were chosen, as previous studies have shown [10][11][12] healthseeking differences and use of home care hours for both. Place of birth was selected, to address concerns about difficulties for immigrants in seeking social service based on language difficulties, cultural differences in health-seeking behavior, and lack of societal inclusion [13,14].…”
Section: Introductionmentioning
confidence: 99%